Paper 05: Glenoid Labral Tears are associated with Increased Neurofilament Innervation. Issue 5 (31st May 2022) - Beretov, Julia; Marvi, Salman; Lam, Patrick; Murrell, George; Murphy, Geoffrey
Objectives: Pain is a common presentation following glenohumeral labral injuries. However, the source of that pain is undetermined. We aimed to determine if there is a differential expression of nerve fibres around the glenoid labrum and if torn labra have increased neuronal expression compared to untorn labra. Methods: Labral tissue was collected at 3, 5, 9 and 12 o clock during total shoulder arthroplasty (n = 7). Samples were also collected at 3, 5 and 12 o clock during rotator cuff repair (n = 16), anterior labral repair (n = 6), type II superior labral anterior to posterior (SLAP) repair (n = 4) and capsular release for idiopathic capsulitis (n = 5). Sections were immunostained with antibodies to neurofilament, a specific neuronal marker which is used to identify central and peripheral nerve fibres, and the concentration and intensity of immunostained-positive cells assessed. Results: The concentration of neurofilament staining was similar in the superior, anterior, posterior and inferior glenoid labrum in untorn labra (8 neurofilament expressing cells/mm 2, p > 0.05). Torn labra exhibited a 3-4-fold increase in neuronal expression which was isolated to the location of the tear in SLAP (p = 0.09) and anterior labral tears (p = 0.02). The concentration of neurofilament expressing cells in torn glenoid labrum samples were comparable to the glenoid labrum of adhesive capsulitis samples (p > 0.05). Figure 3 . Mean (SD) neurofilament expressing cells per mm 2 at 12 o'clock (A ), 3 o'clock (B ) and 5 o'clock (C ) using labral tissue from patients with either a; RCT (n = 16), anterior labral tear (n = 6), SLAP tear (n = 4) or a frozen shoulder (n = 5). *p <0.05 compared using a one-way ANOVA with post-hoc analysis. Conclusions: This study supports the hypothesis that following a traumatic tear of the anterior or superior labrum, the labrum in that region becomes populated with new nerves fibres and that these fibres are likely to be responsible for many of the symptoms noted by patients with superior (SLAP) and/or anterior labral (Bankart) tears.